2015
DOI: 10.1002/jcp.24863
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of SAHA and Parthenolide in MDA‐MB231 Breast Cancer Cells

Abstract: The sesquiterpene lactone Parthenolide (PN) exerted a cytotoxic effect on MDA-MB231 cells, a triple-negative breast cancer (TNBC) cell line, but its effectiveness was scarce when employed at low doses. This represents an obstacle for a therapeutic utilization of PN. In order to overcome this difficulty we associated to PN the suberoylanilide hydroxamic acid (SAHA), an histone deacetylase inhibitor. Our results show that SAHA synergistically sensitized MDA-MB231 cells to the cytotoxic effect of PN. It is notewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 49 publications
1
45
0
Order By: Relevance
“…They claimed that pre-treatment of MDA-MB231 cells with SAHA sensitized the cells to the cytotoxic effect of PN (62), so PN and SAHA acted synergistically in order to fight against TNBC cells (55). Moreover, they demonstrated that SAHA treatment leads to acetylation of lysine residues in the NH 2 -terminal tails of histones H3 and H4 and these findings were in accordance to other studies (63,64).…”
Section: Hdac Inhibitors As Anti-cancer Agentssupporting
confidence: 70%
See 4 more Smart Citations
“…They claimed that pre-treatment of MDA-MB231 cells with SAHA sensitized the cells to the cytotoxic effect of PN (62), so PN and SAHA acted synergistically in order to fight against TNBC cells (55). Moreover, they demonstrated that SAHA treatment leads to acetylation of lysine residues in the NH 2 -terminal tails of histones H3 and H4 and these findings were in accordance to other studies (63,64).…”
Section: Hdac Inhibitors As Anti-cancer Agentssupporting
confidence: 70%
“…Finally, it has been found that SAHA and PN combined therapy induced a decrease of the expression levels of beclin-1, a protein involved in autophagosome formation (55). Previous studies have shown that beclin-1 is cleaved by caspases (67).…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 97%
See 3 more Smart Citations